PENERAPAN THINK PAIR SHARE UNTUK PENINGKATAN HASIL BELAJAR PADA MATERI UNSUR PEMBANGUN TEKS CERITA PENDEK - SUJARWANTO SUJARWANTO (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2022)
This study aims to apply think pair share to improve learning outcomes on the material elements of literary works in short story texts in grade 9A of SMP Negeri 1 Siwalan. Short stories are favorite reading for students because they are short, dense, and in accordance with everyday life. However, the pre-cycle test results are still below the KKM. This indicates that students have not mastered the elements of short story building. After conducting research for two cycles, each cycle has two meetings. Based on the results of the test at the think pair share stage, the end of the cycle test, observations, questionnaires, and interviews, student data were obtained. in cycle 1 meeting 1 students who obtained learning outcomes of 75 or more at the think stage 28%, pair 62%, and share 88%, meeting 2 stage think 6%, pair 22%, and share 88%. Meanwhile, in the second cycle of meeting 1 students who obtained learning outcomes of 75 or more at the 97% think stage, 100% pair, and 100% share, the second meeting of the 100% think stage, 100% pair, and 100% share. Students who get a score of 75 in cycle 1 are 66% and in cycle 2 are 88%. The average student learning outcomes in cycle 1 is 74.22 and in cycle 2 is 83.91. The student attitude assessment is obtained from self-assessment of religious attitudes and social attitudes. Religious attitudes in cycle 1 meeting 1 obtained a score of 3.28 meeting 2 obtained a score of 3.59, cycle 2 meeting 1 obtained a score of 3.78 meeting 2 obtained a score of 3.86, social attitudes in cycle 1 meeting 1 obtained a score of 3.33 meetings 2 obtained a score of 3.26, cycle 2 meeting 1 obtained a score of 3.43 meeting 2 obtained a score of 3.74. ABSTRAKPenelitian ini bertujuan untuk menerapkan think pair share untuk meningkatkan hasil belajar pada materi unsur pembangun karya sastra dalam teks cerita pendek di kelas 9A SMP Negeri 1 Siwalan. Cerita pendek merupakan bacaan yang digemari siswa karena isinya singkat, padat, dan sesuai dengan kehidupan sehari-hari. Namun, hasil tes prasiklus masih di bawah KKM. Hal tersebut menandakan bahwa siswa belum menguasai unsur pembangun cerita pendek. Setelah diadakan penelitian selama dua siklus, setiap siklusnya dua pertemuan. Berdasarkan hasil tes pada tahap think pair share, tes akhir siklus, pengamatan, angket, dan wawancara diperoleh data siswa. pada siklus 1 pertemuan 1 siswa yang memperoleh nilai hasil belajar 75 atau lebih pada tahap think 28%, pair 62%, dan share 88%, pertemuan 2 tahap think 6%, pair 22%, dan share 88%. Sedangkan pada siklus 2 pertemuan 1 siswa yang memperoleh nilai hasil belajar 75 atau lebih pada tahap think 97%, pair 100%, dan share 100%, pertemuan 2 tahap think 100%, pair 100%, dan share 100%. Siswa yang memperoleh nilai hasil belajar 75 ? pada siklus 1 sejumlah 66% dan pada siklus 2 sejumlah 88%. Rata-rata hasil belajar siswa pada siklus 1 sebesar 74,22 dan pada siklus 2 sebesar 83,91.Penilaian sikap siswa diperoleh dari penilaian diri sikap religius dan sikap sosial. Sikap religius pada siklus 1 pertemuan 1 memperoleh skor 3,28 pertemuan 2 memperoleh skor 3,59, siklus 2 pertemuan 1 memperoleh skor 3,78 pertemuan 2 memperoleh skor 3,86, Sikap sosial pada siklus 1 pertemuan 1 memperoleh skor 3,33 pertemuan 2 memperoleh skor 3,26, siklus 2 pertemuan 1 memperoleh skor 3,43 pertemuan 2 memperoleh skor 3,74.